Defending Due Process: The Case for Abolishing the Show-Up Line-Up - Stephen Bertelsman (Washington University Journal of Law and Policy, 2022)
The “show-up”—a single suspect being presented to witnesses for identification—is a common tool employed by police in an investigation. While the tactic seems helpful on its face, the show-up can be a problematic and unreliable tactic that creates a suggestive outcome for the witness, who has often only had a fleeting view of the suspect. Despite repeated and sharp attacks on show-up identifications, police continue to employ and courts continue to admit show-ups. This Note advocates for the enactment of a statute to abolish police use of the show-up. Bertelsman argues that the current tests utilized by courts to determine the validity of a show-up are flawed and allow well-intentioned judges to admit suggestive identifications and make it easy for police officers to construct an “exigent circumstance” defense to circumvent safeguards. Bertelsman concludes that his proposal for a strict statutory regulation abolishing the show-up is the only way to end this damaging practice and preserve a defendant’s due process rights.
Keywords: Show-up; Witness Identification; Suggestive Identification; Exigent Circumstance; Due Process Right